The association of periodontal disease with oral malodor before and after antibiotic rinse using FITSCAN® breath checker: A clinical study - M P Singh; Preetika Bansal; Satinder Kaur (Wolters Kluwer Medknow Publications, 2014)
Context: The term "oral malodor" is used to describe a foul or offensive odor emanating from oral cavity. Dentist is the first professional whom individuals turn up for help. Gram-negative anerobic pathogens implicated in periodontal disease have also been linked to oral malodor. A semi-conductor, hand-held gas sensor with 6 levels of display, brand name FITSCAN® Breath Checker (Tanita Corporation, USA) used to detect oral malodor. Antibiotics are now being tried and used to treat oral malodor and periodontal disease. Aims: To evaluate the association between malodor and periodontal status of patients before and after antibiotic rinse. Materials and Methods: Systemically healthy subjects were divided into three groups - control group, gingivitis group, periodontitis group. Measurement of oral malodor was done by FITSCAN® Breath Checker. Antibiotic rinse preparation containing metronidazole was given to patients. An association between oral malodor and periodontal disease status of patients was determined. Statistical analysis used: For intragroup analysis paired "t" test and for intergroup analysis of halitosis and gingival index "Kruskal-Wallis test" and "Mann-Whitney U test" were applied. Results: Intragroup - Statistical significant decrease in halitosis, Gingival Index (GI) at baseline and 14 days in persons with gingivitis and periodontitis group, no statistical significant decrease in pocket depth before and after antibiotic rinse. Intergroup - Statistical significant decrease in Gingival Index status at baseline and 14 days in both gingivitis andperiodontitisgroups. Conclusion: Strong correlation exists between malodor and periodontal status and antibiotic rinse is effective in reducing oral malodor.